Thai Literature Instruction Based on Character Education Approach to Enhance Reading Comprehension and Self-Responsibility of Pre-Cadet Students - Kongkhao, Saranyoo; Sakolrak, Soison Sakolrak (Journal of Education Studies, Chulalongkorn University, 2025)
The purposes of this research were to: 1) develop a Thai literature instruction approach based on character education principles, and 2) study the effects of this educational approach to enhance reading comprehension and self-responsibility. The sample consisted of 33 pre-cadet students studying in their first year. The participants were chosen via cluster random sampling method. The instruments for data collection were 1) a test of self-responsibility knowing and reading comprehension, 2) a questionnaire feeling toward self-responsibility, and 3) a self-responsibility evaluation form. The instruments for experiment were lesson plans for teaching Thai literature based on a character education approach. The data were analyzed using arithmetic mean, standard deviation, dependent simple t-test, and the qualitative data were analyzed using content analysis. The results of this research were as follows: 1) the instructional model comprised four elements: (1) lesson objectives, (2) content and media, (3) learning activity procedures which are the preparation of selecting literature to enhance responsibility, enhancing the importance of responsibility awareness, and understanding through reading literature to enhance responsibility and (4) assessment, and 2)the results of this Thai literature instruction model after implementation was found. The students displayed a higher level of reading comprehension abilities and self-responsibility at the .05 level of significance.